Safavid architecture as a historical precedent and design paradigm to the aesthetic of contemporary Iranian architecture / Bahram Shahedi - Bahram, Shahedi (2013)
The architectural aesthetic design has been a powerful influence and a rich source of reference to the formation of novel ideas throughout the early stages of architectural history. The implementation of architectural aesthetic design by applying historical precedents has generated significant impact on the overall quality of the built environment. A notable historical architectural precedent known as the Isfahani style, during the era of Safavid Architecture is proposed in this doctoral study to possess highly attractive aesthetic values with respect to the current contemporary Iranian architecture, specifically Iranian architectural designs built in the last five decades. The main objective of this study was to investigate the architectural aesthetic design features experienced by the users and nonusers of the Safavid buildings. Additionally, to identify and validate the design criteria that make Safavid Architecture still highly useful and relevant in terms of how it expresses architectural aesthetic design features. Furthermore, the values and attributes used in the design processes found in today’s contemporary architectural phenomenon possess little evidence of a design approach that places importance on the architectural aesthetic experience. Hence, this research explored the historical precedent of Safavid Architecture by examining chosen historical buildings, using qualitative multiple case study techniques and by collecting data from multiple sources for each of the case studies. The sources included direct observational data collected through video and audio documentation of the cases being studied, semi-structured interviews with experts, and a perception study survey using questionnaires given to users and nonusers of the Safavid architectural buildings. The findings, obtained from experts’ interviews were used to validate the findings obtained from users and nonuser’ perceptions through cross checking and triangulation. Research findings and results were analyzed using quantitative and qualitative approaches. Data analysis included categorization of themes defined by a theoretical framework through content analysis of patterns and a systematic redefinition of categories after validation. The veracity of the research was improved by triangulating the data obtained from multiple sources. The findings suggested positive and favorable analysis results, lending proof to the premise of the study. Additionally, three chief themes were uncovered with its unique design values, attributes and approach, which could be used to form the basis of a historical, architectural precedent. The analyzed results highlight the importance of aesthetic design characteristics, which include systematic process, and design concept, interaction with spatial and physical context, identity, meaning, rationalism, structural honesty, minimalism, unity, pattern, ordering principle, and paradigm of design. In conclusion, the research provided a framework for a holistic theoretical explanation, summed up based on research findings related to the issue being researched. Keywords: Historical architectural precedents, Safavid Architecture, Contemporary Iranian Architecture